Effect of SGLT2 inhibitors on cardiovascular, renal and safety outcomes in patients with type 2 diabetes mellitus and chronic kidney disease: A systematic review and meta‐analysis. Issue 5 (4th March 2019) - Toyama, Tadashi; Neuen, Brendon L.; Jun, Min; Ohkuma, Toshiaki; Neal, Bruce; Jardine, Meg J.; Heerspink, Hiddo L.; Wong, Muh Geot; Ninomiya, Toshiharu; Wada, Takashi; Perkovic, Vlado
Abstract : Aim: The use of sodium glucose co‐transporter 2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) has been limited, primarily because glycaemic efficacy is dependent on kidney function. We performed a systematic review and meta‐analysis to assess the efficacy and safety of SGLT2 inhibitors in patients with T2DM and CKD, defined as estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 . Materials and methods: We searched MEDLINE, EMBASE and the Cochrane Library until 7 August 2018 and websites of the US, European and Japanese regulatory authorities until 27 July 2018 for data from randomized controlled trials of SGLT2 inhibitors that included reporting of effects on biomarkers, cardiovascular, renal or safety outcomes in individuals with T2DM and CKD. Random effects models and inverse variance weighting were used to calculate relative risks with 95% confidence intervals. Results: Data were obtained from 27 studies with up to 7363 participants involved. In patients with T2DM and CKD, SGLT2 inhibitors lowered glycated haemoglobin (−0.29%; 95% CI, −0.39 to −0.19) as well as blood pressure, body weight and albuminuria. SGLT2 inhibition reduced the risk of cardiovascular death, nonfatal myocardial infarction or nonfatal stroke (RR, 0.81; 95% CI, 0.70‐0.94) and heart failure (RR, 0.61; 95% CI, 0.48‐0.78), without a clear effect on all‐cause mortality (HR, 0.86; 95% CI, 0.73‐1.01). These agents also attenuated the annual decline in eGFR slope (placebo‐subtracted difference of 1.35 mL/1.73 m 2 /y; 95% CI, 0.78‐1.93) and reduced the risk of the composite renal outcome (HR, 0.71; 95% CI, 0.53‐0.95). There was no evidence of additional risks with SGLT2 inhibition in CKD beyond those already known for the class, although heterogeneity was observed across individual agents for some safety outcomes. Conclusion: Currently available data suggest that, despite only modest reductions in glycated haemoglobin, SGLT2 inhibitors reduce the risk of cardiovascular and renal outcomes in patients with T2DM and CKD, without clear evidence of additional safety concerns.